Outcomes of paroxysmal atrial fibrillation ablation studies are affected more by study design and patient mix than ablation technique. (30th October 2018) - Ferreira‐Martins, João; Howard, James; Al‐Khayatt, Becker; Shalhoub, Joseph; Sohaib, Afzal; Shun‐Shin, Matthew J.; Novak, Paul G.; Leather, Rick; Sterns, Laurence D.; Lane, Christopher; Lim, Phang Boon; Kanagaratnam, Prapa; et al.
Abstract: Objective: We tested whether ablation methodology and study design can explain the varying outcomes in terms of atrial fibrillation (AF)‐free survival at 1 year. Background: There have been numerous paroxysmal AF ablation trials, which are heterogeneous in their use of different ablation techniques and study design. A useful approach to understanding how these factors influence outcome is to dismantle the trials into individual arms and reconstitute them as a large meta‐regression. Methods: Data were collected from 66 studies (6941 patients). With freedom from AF as the dependent variable, we performed meta‐regression using the individual study arm as the unit. Results: Success rates did not change regardless of the technique used to produce pulmonary vein isolation (PVI). Neither was adjunctive lesion sets associated with any improvement in outcome. Studies that included more males and fewer hypertensive patients were found more likely to report better outcomes. The electrocardiography method selected to assess outcome also plays an important role. Outcomes were worse in studies that used regular telemonitoring (by 23%; P < 0.001) or in patients who had implantable loop recorders (by 21%; P = 0.006), rather than those with the less thorough periodic Holter monitoring. Conclusions: Outcomes of AF ablation studies involving PVI are not affected by the technologies used to produce PVI. Neither do adjunctive lesion sets change the outcome. Achieving high success rates in these studies appears to be dependent more on patient mix and on the thoroughness of AF detection protocols. These should be carefully considered when quoting the success rates of AF ablation procedures that are derived from such studies.